The road not taken: Competition and the R&D portfolio - Igor Letina (University of Zurich, Department of Economics, 2015)
This article examines the effects of market structure on the variety of research projects undertaken and the amount of duplication of research. A characterization of the equilibrium market portfolio of R&D projects and the socially optimal portfolio is provided. It is shown that a merger decreases the variety of developed projects and decreases the amount of duplication of research. An increase in the intensity of competition among firms leads to an increase in the variety of developed projects and a decrease in the amount of duplication of research.
Keywords: L13; L22; O31; 330; Innovation; competition; R&D portfolio; market structure; Innovation; Wettbewerb; Marktstruktur; Portfolio-Management